Empathy in High School Students - Iyus Yosep; Ai Mardhiyah; Rohman Hikmat (Fakultas Kedokteran Universitas Sriwijaya, 2024)
Empathy is an important skill that plays a role in the social and emotional development of adolescents and contributes to healthy and harmonious interpersonal relationships. The decline in empathy levels in adolescents today is a concern, especially in social contexts such as interactions in high school (SMA). Empathy is also key to preventing negative behaviors such as bullying and improving communication and collaboration skills. Therefore, it is important to understand students' empathy levels as a first step in developing appropriate interventions. This study aims to describe the level of empathy in high school students in Bandung. This study used a descriptive design with a total sampling technique, involving 100 respondents. Data were collected using the Basic Empathy Scale (BES) questionnaire consisting of 20 statements to measure affective and cognitive empathy. The validity test of the instrument showed a value between 0.567 and 0.812, while its reliability was measured by the Cronbach alpha coefficient of 0.85 for affective empathy and 0.79 for cognitive empathy. Data analysis was carried out using frequency distribution to describe the characteristics and levels of empathy of respondents. The results of the study showed that the average level of empathy of students was 51.82, with the majority of students in the moderate empathy category (51%). This finding indicates that most students have adequate empathy skills, but there is still room for further development. Factors such as family background, academic pressure, and the influence of social media also contribute to the level of empathy shown by students. This study is expected to support the development of educational policies that focus on strengthening students' character and mental health.